'Is It Family or Politics?' Reflections on Gender and the Modern Tamil Subjectivity Constitution in the Discourse of C. N. Annadurai. (December 2018) - Sujatha, G.
This article attempts to investigate the relationship between the domestic and the politics in the modern Tamil subjectivity constitution during the period spanning from the 1940s to the 1960s. More specifically, it takes up the political discourse of C. N. Annadurai—a significant founding member of the Dravida Munnetra Kazhagam (DMK) and a man who played a decisive role in shaping the culture and politics of the state—and attempts to examine the spatial tension, that is, the fusion and commonalities between the domestic sphere and political space in modern Tamil subjectivity construction and the implications it had for gender.